Genetic Explorations for Feature Selection - Anushya, A (International Journal of Computer Sciences and Engineering, 2019)
In this research, Genetic Algorithm is used for feature selection. Genetic Algorithm has been combined with local search, named as Memetic Algorithm and an algorithm is proposed and named as Compound Featuristic Genetic Algorithm. Next, based on, Class Dependent Feature Subset Selection, an algorithm is proposed namely, Core Featuristic Genetic Algorithm. The performance analyses of existing and proposed feature selection algorithms are functioned on heart dataset to predict the heart disease with minimum number of features. Finally, Fuzzy Decision Tree, Fuzzy Naive Bayes and Fuzzy Neural Networks are applied to the reduced set of the Heart dataset, obtained for classification accuracy.